2023
DOI: 10.1532/hsf.5211
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Direct Coronary Artery Bypass Versus Percutaneous Coronary Intervention for Isolated Left Anterior Descending Artery Stenosis: An Updated Meta-Analysis

Abstract: Background: The optimal revascularization strategy for isolated left anterior descending (LAD) coronary artery lesion between minimally invasive direct coronary artery bypass (MIDCAB) and percutaneous coronary intervention (PCI) remains controversial. This updated meta-analysis aims to compare the long- and short-term outcomes of MIDCAB versus PCI for patients with isolated LAD coronary artery lesions. Methods: The Pubmed, Web of Science, and Cochrane databases were searched for retrieving potential publicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…In another meta-analysis comparing MIDCAB and PCI, there was no significant difference in the long-term mortality. However, the MIDCAB group showed a significant reduction in the TVR and MACCE rates 34,35) . Manuel et al reported that the 20-year survival rate of MIDCAB patients with single-vessel LAD disease remained nearly the same as that of an age-and gender-matched normal population 36) .…”
Section: Long-term Outcomes Of Midcabmentioning
confidence: 87%
“…In another meta-analysis comparing MIDCAB and PCI, there was no significant difference in the long-term mortality. However, the MIDCAB group showed a significant reduction in the TVR and MACCE rates 34,35) . Manuel et al reported that the 20-year survival rate of MIDCAB patients with single-vessel LAD disease remained nearly the same as that of an age-and gender-matched normal population 36) .…”
Section: Long-term Outcomes Of Midcabmentioning
confidence: 87%